Social Prescribing—An Effort to Apply a Common Knowledge: Impelling Forces and Challenges - Islam, M. Mofizul (Frontiers in Public Health, 2020)
In recent times, social prescribing has been introduced in some countries, and substantially in the U.K. The objective of this scheme is to offer non-medical care mainly to primary care patients. Although the idea of this scheme is not new, its formalisation is. Using a narrative synthesis of peer-reviewed and grey literature, this article discusses the social prescribing scheme, some of its compelling aspects and challenges in offering non-medical care, particularly regarding referrals being made from primary care settings. The social prescribing scheme has several impelling forces that include its potential to turn primary care to primary healthcare, tackle social determinants of health and social needs, improve wellbeing and physical health, offer person-centred care, strengthen preventive care, and bridge healthcare organisations with the third sector. This scheme also faces several challenges including service standards and boundaries, sustainability, availability of appropriate services, low engagement of clients and insufficient evidence. While this scheme lacks validated evidence, it is theoretically compelling. Given that the demand for non-medical care is growing in most societies and that the usefulness of non-medical care is gaining prominence, social prescribing is likely to continue to proliferate.